Inequality and violence a re-appraisal of Man, the state and war - Beyer, Cornelia (Ashgate Publishing Company, 2014)
This book reflects on the arguments presented in Man, the State and War from a contemporary perspective. Do Waltz's ideas still hold firm ground in the discipline? The book alerts to the perceived necessity of combining conceptions of governance and authority with considerations on the reduction of inequality at the individual.